Strategi Pengembangan Usaha Ternak Sapi Potong Untuk Meningkatkan Pendapatan Petani Di Desa Bangkali Kecamatan Watopute Kabupaten Muna - Wa Ode Sitti Nur Sahida Mada; Bahari Bahari; Rosmawaty Rosmawaty (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
This research aims to determine strategies for developing beef cattle farming to increase farmers' income in Bangkali village, Watopute District, Muna Regency. Determining the research area was carried out purposively with the consideration that Bangkali Village, Watopute District, Muna Regency has great potential for the development of beef cattle. There were four informants in this research, including the Animal Husbandry Service, Breeders, Extension Institute and Financial Institutions. Data analysis uses Analitycal Hierarchy Process (AHP) analysis. The results of the research show that the priority strategy for developing the beef cattle business to increase farmers' income in Bangkali Village, Watopute District, Muna Regency is capital/finance weight 316, Increasing Marketing weight 275, Increasing human resources weight 206, and increasing production weight 203 with an inconsistency of 0.02